Assessment of Knowledge, Awareness, and Use of Family Planning Methods Among Residents in Iringa Municipality - M. Mgaya , Catherine; R. Mgonja, Frida (International Research in Education, 2023)
A cross-sectional descriptive study was conducted in the Iringa Municipality with 100 women of childbearing age aged 18 to 45 years. Levels of knowledge and awareness of family planning methods were surveyed using a self-administered questionnaire. As a result, it was found that the majority of 94(94%) of the surveyed population said they were well-informed about family planning methods and had good attitudes and awareness of contraceptives. Of the methods presented, male condoms, injections, and implants were familiar and used by the majority of participants. Of the 100 participants, 85(85%) used modern family planning techniques and 71(83.5%) of them reported having used services at a health facility. However, the remaining 15(15%) of respondents indicated that they did not use family planning for religious and cultural reasons. Modern contraceptive technology is available, accessible, and proven to be used. Therefore, more education is needed for communities on the importance of using permanent modern strategies, including sterilization. Getting men involved is also important.